MATERIAL INSULASI TERHADAP EFEK KEHILANGAN PANAS PADA JALUR PIPA PANAS BUMI - Samsol Samsol; Kris Pudyastuti; Nicko Matthe Lie (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2019)
Heat loss which occured because heat transfer from high temperature to low temperature is one of major problem in piping design in geothermal. Insulation used to solve the problem. These analysis carried out in 18 inch pipeline in steam field. Calcium silicate, rockwool, and foam glass is selected as 3 materials in these study. These 3 materials have different thermal conductivity, so ability to withstand heat for each of them is different. This research used to determine the best material to solve heat loss. Rockwool is the best material from the other 2